Consensus recommendations from the Czech Head and Neck Cancer Cooperative Group (2019): definition of surgical margins status, neck dissection reporting, and HPV/p16 status assessment - Vošmik, Milan; Klozar, Jan; Laco, Jan; Hlavy, Česká Kooperativní Skupina Pro Nádory; Krku (Ceskoslovenska patologie, 2021)
The Czech Head and Neck Cancer Cooperative Group (CHNCCG) held a meeting in Tabor on 11-12 October 2019 with the aim of reaching an interdisciplinary consensus on some controversial points where international unity is absent. The meeting resulted in recommendations on resection margin size terminology (definition of terms: negative margin, close margin and positive margin) and on the adoption of terminology for neck dissections reporting according to the International Recommendation of the International Head and Neck Scientific Group and on assessment of HPV/p16 status in head and neck tumors.
Keywords: head and neck cancer; nádory hlavy a krku; Consensus; resection margin; lidé; konsensus; Česká republika; resekční okraje; Head and Neck Neoplasms; Papillomavirus Infections; Margins of Excision; Czech Republic; neck dissection; p16; krční disekce; infekce papilomavirem; inhibitor p16 cyklin-dependentní kinasy; Humans; recommendation; Cyclin-Dependent Kinase Inhibitor p16; HPV; guidelines; Neck Dissection